Nitrogen use efficiency and recovery in a wheat-corn rotation under tropical savannah conditions - Galindo, Fernando Shintate [UNESP]; da Silva, Edson Cabral; Pagliari, Paulo Humberto; Fernandes, Guilherme Carlos [UNESP]; Rodrigues, Willian Lima [UNESP]; Biagini, Antônio Leonardo Campos [UNESP]; Baratella, Eduardo Bianchi [UNESP]; da Silva Júnior, Castro Alves [UNESP]; Moretti Neto, Mário João [UNESP]; Muraoka, Takashi; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP] (Springer Nature, 2021)
Stable isotopes (e.g., 15N) can be used to develop best practices for fertilizer management in cereal crops under tropical conditions. The objectives of this study were to determine the N contribution from fertilizer and soil to wheat and corn grown in rotation and the residual N contribution from fertilizer applied to wheat and carried over to corn under Brazilian savannah conditions. This study was established in a no-till system on Rhodic Haplustox soil in a randomized complete block design with four replications. The N treatments applied to the wheat crops were 0, 20, 40, 60, 80 and 160 kg (urea-15N) ha−1. The residual effects of N on the succeeding corn crop were evaluated. During the corn phase, two additional treatments were included: a control (0 N) and a treatment with 160 kg N ha−1. Regression analysis showed that the highest estimated wheat yield (5415 kg ha−1) was observed with the application of 114 kg N ha−1. Significant effects from the residual N were observed in the corn shoot biomass and straw N uptake. On average, the recovery rate of the urea N fertilizer was 34% for wheat, and the residual urea N fertilizer use in corn (when applied to wheat) was less than 5% of the amount initially applied. The effect of the residual N was not enough to meet the N demands of the succeeding corn crop. The results of this study provide producers and the scientific community with good estimates of nitrogen use efficiency for wheat and corn.
Keywords: Efficiency of nitrogen fertilization; Nitrogen-15; Residual effect of N; Triticum aestivum L; Zea mays L